2014
DOI: 10.1021/jo5021294
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Synthetic Studies with Tetravinylethylenes

Abstract: Computational and experimental studies offer fresh insights into the neglected tetravinylethylene class of compounds. Both the structures and the outcomes of exploratory reactions of the parent hydrocarbon are predicted and explained in detail through high-level composite ab initio MO G4(MP2) computational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The first synthesis of TVE, a landmark contribution from the classical era of unsaturated hydrocarbon chemistry, was reported by Skattebøl and co‐workers in the 1960s . We recently disclosed the first preparatively useful approach to TVE, a one‐step, multi‐gram scale synthesis, and demonstrated that the hydrocarbon is bench‐stable when stored as a neat liquid . The one‐step synthesis of TVE (Scheme , 1 a ) utilized a Pd 0 ‐catalyzed fourfold Stille cross‐coupling sequence between tetrachloroethylene 2 and vinyltributylstannane 3 a .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first synthesis of TVE, a landmark contribution from the classical era of unsaturated hydrocarbon chemistry, was reported by Skattebøl and co‐workers in the 1960s . We recently disclosed the first preparatively useful approach to TVE, a one‐step, multi‐gram scale synthesis, and demonstrated that the hydrocarbon is bench‐stable when stored as a neat liquid . The one‐step synthesis of TVE (Scheme , 1 a ) utilized a Pd 0 ‐catalyzed fourfold Stille cross‐coupling sequence between tetrachloroethylene 2 and vinyltributylstannane 3 a .…”
Section: Methodsmentioning
confidence: 99%
“…The one‐step synthesis of TVE (Scheme , 1 a ) utilized a Pd 0 ‐catalyzed fourfold Stille cross‐coupling sequence between tetrachloroethylene 2 and vinyltributylstannane 3 a . In addition to the parent TVE, five symmetrically substituted TVEs 1 b were similarly prepared using substituted alkenyltributylstannanes 3 b in the exhaustive Stille cross‐coupling process …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations